Case of Segmental Arterial Mediolysis. (13th March 2018) - Britto, Maneka M; Lukies, Matthew; Milne, Charles; Joseph, Timothy; Lee, James C
Abstract : Segmental arterial mediolysis (SAM) is a rare, non-inflammatory, vascular condition that predominantly affects medium-sized to large-sized abdominal arteries and can present with haemorrhage into the abdominal cavity. We report the case of a patient with SAM of the coeliac, splenic, renal and gastroduodenal arteries in whom endovascular coil embolisation was successfully used to treat a bleeding gastroduodenal artery pseudoaneurysm.